The role of self-improvement in a person’s spiritual development and its mechanisms - Romanovsky, A.; Mikhailichenko, V. (Problems of Engineer-Pedagogical Education, 2018)
The article represents the view on the notion of human spirituality and its role in society’s spiritual development. A human is seen as a cosmoplanetary being possessing energy-andinformation properties and obeying cosmic laws in his/her development. Evolvement of a person’s consciousness is maintained at this level on the basis of this person’s self-perfection. There is substantiated the need in changing the mode of thinking from the extravert to the introvert, the one directed inside oneself. The methodology of this process is the so-called “work on oneself” which enables mastering practices of psychic and spiritual self-perfection which are closely interconnected. Hence the need to pay more attention in the course of teaching to selfconsciousness and self-learning, to teach young people to create their actual and ideal self-image and strive for achieving the latter through self-development and self perfection. One needs understand consciousness mechanisms and direct it at self perfection through employment of will, thought concentration, directed imagination. Controlled imagination can open a person’s mind, activate their feelings and belief. It is necessary to learn to construct one’s imagination, to control it, and to govern it. A great role is played by autosuggestion. The article contains the ways of mastering practices of psychic self-perfection. There are shown the need in using persuasion, bright examples of spiritual power’s influencing people’s state of mind, way of life, and moral behavior.